2023
DOI: 10.3389/fpls.2022.1065627
|View full text |Cite
|
Sign up to set email alerts
|

Small G Protein StRab5b positively regulates potato resistance to Phytophthora infestans

Abstract: Rabproteins are the largest members of the small G protein family and are widely distributed in eukaryotes. It comprises eight subfamilies and is responsible for regulating vesicle transport, plant growth and development, and biotic and abiotic stress responses. In this study, the small G protein gene StRab5b was cloned from potato, and its biological information, expression profile and induced expression level, overexpression and gene silencing were examined on regulating potato resistance to Phytophthora inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Besides, our results also showed that defense enzymes of SOD, PPO, POD, PAL, CAT and β-1,3-GA exhibited high activities in diseased roots and stems (Fig. 6), which indicated that defense enzymes participated in the signaling pathway of the plant-pathogen interactions [56]. When plants were invaded by pathogens, reactive oxygen species (ROS) rapidly accumulated and caused programmed cell death and hypersensitive response of plants.…”
Section: Discussionmentioning
confidence: 72%
“…Besides, our results also showed that defense enzymes of SOD, PPO, POD, PAL, CAT and β-1,3-GA exhibited high activities in diseased roots and stems (Fig. 6), which indicated that defense enzymes participated in the signaling pathway of the plant-pathogen interactions [56]. When plants were invaded by pathogens, reactive oxygen species (ROS) rapidly accumulated and caused programmed cell death and hypersensitive response of plants.…”
Section: Discussionmentioning
confidence: 72%
“…However, most of these candidates for MAS need to be validated in dedicated mechanistic studies. A recent study showed that an accumulation of Small G protein StRab5b reduced the lesions on infected potato leaves [205], but it remains to be seen how this alteration impacts the yield and other economically important traits. The most interesting part of the proteome resides in post-translational modifications.…”
Section: Candidate Proteins For Masmentioning
confidence: 99%
“…The effectiveness of these endogenous S. tuberosum peptides against P. infestans is unclear, and further research is needed. However, foreign or synthetic antimicrobial peptides have been found to provide resistance against P. infestans, including syringomycin E and syringopeptin 25A from Pseudomonas syringae [205], Stellaria media hevein [215], and the synthetic peptide NoPv1 [216].…”
Section: Antimicrobial Peptides-prospective Targets For Enhanced Resi...mentioning
confidence: 99%